Book Review: The Life and Death of a Rural American High School: Farewell Little Kanawha - Larry Cuban (Journal of Research in Rural Education, 1995)
In The Life and Death ofa Rural High School: Farewell Little Kanawha, Alan DeYoung records the three quarters of a century history of Burnsville High and Middle Schools in Braxton County, West Virginia. "Little K", as he and others have called the school (after the nearby Little Kanawha River), was built in 1915 as a first- through twelfth-grade school divided into two units of grades 1-8 and 9-12. The two-unit school served as the town elementary school and the district high school until the early 1950s when the decline in population accelerated and the county school board began consolidating smaller outlying one- and two-room rural schools. The students bused into "Little K" and nearby high schools found the facilities limited.